Role of UNHCR in case of asylum seekers, refugees and stateless persons -- the case study of Turkey - Unzeitigová, Klára; Votoupalová, Markéta; Kuchařová, Alžběta; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
Inspired by the Kratochvíl, Cibulková and Beník´s model of actorness, the thesis explores the framing power of UNHCR. The critical discourse analysis introduced by Norman Fairclough is applied in order to analyze the textual, contextual and sociocultural dimension of the UNHCR framing power. The case of Turkey was chosen for this study due to the current situation and the fact that Turkey is one of the biggest hosting country in the refugees´ crisis. Through the critical discourse analysis, the thesis explores whether UNHCR is considered as a framing actor in the case of asylum seekers, refugees and stateless people in Turkey. The analysis shows that UNHCR is globally respected and takes important part in the issue. However, not all of the international organizations refer to UNHCR as the lawmaker and the initiator of debates in the issues mentioned above.
Vedoucí práce: Markéta Novotná
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: mezinárodní politika a diplomacie [obor dipl. práce]; diplomové práce; master's theses